Manual de procedimento operacional padrão para o exame angiofluoresceinografia do Setor de Retina do Departamento de Oftalmologia e Ciências Visuais da Universidade Federal de São Paulo - Fernandes, Rosa Candido [UNIFESP] (2021)
Introduction: Several tests are necessary for the evaluation of the retina. Retinal angiography with sodium fluorescein also called fluorescent retinal angiography or fluorescein retinography is an important exam for the diagnosis of many retinal conditions. The exam is performed by obtaining retinal images combined with intravenous administration of sodium fluorescein. Purpose: To elaborate a Standard Operating Procedure Manual (POP) for the Retina Division to improve processes involved in the execution of this exam in our department. Methods: The study was guided by the PDCA cycle: planning (P), implementation and development (D), critical performance analysis (C) and corrective action for dysfunctions or assumption of innovations (A). The management of this process allows the identification of innovation opportunities, reduces variation in processes and prevents errors. Questionnaires were administered to patients submitted to this exam before and after the implementation of new guidelines. Results: During the study, questionnaires were applied to 30 patients who had already been guided through the form used in the Retina Division to measure patient satisfaction in relation to the current orientation process. Guidelines were improved and reviewed by retina specialists from our Department and readily available for implementation. New questionnaires were administered and 100% of the patients were satisfied with the results. A new POP was developed and implemented in the division. Conclusion: A new Standard Operating Procedure Manual for retinal angiography was developed and as well as new guidelines were implemented in the Retina Division of our Department.